A Survey of the Economics of Fair Trade - Ana C. Dammert; Sarah Mohan (Institute for the Study of Labor (IZA), 2014)
Fair Trade has spread in developing countries as an initiative aimed at lifting poor smallholder farmers out of poverty by providing them with premium prices, availability of credit, and improved community development and social goods. Fair Trade is also viewed as a niche market for high value products in a context of globalization and trade liberalization policies that affect smallholder farmers in developing countries. The question of whether Fair Trade affects the welfare of rural farmers, however, is particularly contentious. This paper provides a review of the Fair Trade literature, both theoretical and empirical, with a specific focus on the analysis of small-scale producer's welfare in developing countries. Our review shows that while most empirical papers have focused on the impacts of Fair Trade on prices and income, our review highlights the importance of limited market access and changes in productivity. Likewise, little is known about the impacts of Fair Trade on labor markets and human capital investments. Persistent methodological challenges make it challenging, however, to assess the causal impact of this certification and labelling initiative.
Keywords: O19; P46; 330; Fair Trade; developing countries; market efficiency